Vpliv parodontalne bolezni na zdravje pljuč - Petelin, Milan (Medicinski razgledi, 2004)
Pneumonia may be a risky disease in spite of its contemporary treatment with antibiotics. It is the fifth cause of death in the population. The morbidity rate of aspiration pneumonia caused by Gram-negative anaerobic bacteria from the oral cavity or throat is about 30%. The risk for aspiration pneumonia is much greater among alcoholics, intensive care patients, patients after stroke and nursing home residents. Dental plaque is a reservoir of microorganisms anda favourable milieu for the growth of respiratory pathogens. It is therefore possible that patients with periodontal disease are at a higher riskof aspiration pneumonia. The respiratory epithelium can be modified by enzymes and cytokines that are released during periodontal disease and enable the accumulation and multiplication of bacteria on its surface. Oral pathogensmay be aspirated into the pulmonary airways and may cause a pulmonaryinfection. The health status of teeth and periodontal tissues, as well as proper oral hygiene are important preventative procedures for preventing pulmonary infections in high-risk patients.
Keywords: Parodontalne bolezni; Periodontal Diseases; Pljučnica aspiracijska; Dental Plaque; Pneumonia, Aspiration; Zobni plak; zobni karies; Etiology; bacteria; bakterije; pljučnica